Answer:
See below
Step-by-step explanation:
<u>Part A</u>
A vertical stretch takes place when
given that ![|a| > 1](https://tex.z-dn.net/?f=%7Ca%7C%20%3E%201)
<u>Part B</u>
A vertical compression takes place when
given that ![0 < |a| < 1](https://tex.z-dn.net/?f=0%20%3C%20%7Ca%7C%20%3C%201)
<u>Part C</u>
A vertical stretch is different than a horizontal compression:
- In a vertical stretch, the input stays the same, but the output is multiplied by the scale factor
- In a horizontal compression, the output stays the same, but the input is multiplied by the scale factor
<u>Part D</u>
A reflection across the x-axis means that the output, our y-variable, is the opposite sign. This means that all values of
must be negative such that
as mentioned in parts A and B. Also, in part C, since our scale factor is negative, the output is the only one being multiplied by the scale factor.
10% of 75 is 7.5
1% of 75 is .75
.1% of 75 is .075
.5 of 75 is .375
Answer:
x = 200
Step-by-step explanation:
1/5x – 2/3y = 30
substitute in y
1/5x - 2/3(15) = 30
multiply
1/5x - 10 = 30
isolate the variable
1/5x = 40
multiply each side by 5
x = 200
From the calculation, the growth rate is 0.88.
<h3>What is the growth rate?</h3>
To find the relative growth rate
P1 = Poe^rt
P2 = Poe^rt
Thus;
1920 = Poe^4r ------ (1)
1966080 =Poe^12r -------(2)
P2/P1 gives;
1966080/1920 = Poe^12r/Poe^4r
1024 = e^12r/e^4r
1024 =e^8r
1024 = (e^r)^8
2^10 = (e^r)^8
e^r = 2^1.25
e^r = 2.38
r = ln(2.38)
r = 0.88
The initial size of the culture is;
1920 = Poe^(0.88 * 4)
Po = 1920/e^(0.88 * 4)
Po = 57
The expression for the exact number of bacteria after t hours is
P(t) = 57e^0.08t
The growth (in bacteria per hour) after 9.5 hours is
P(t) = 57e^(0.88 * 9.5)
P(t) = 243544
For the number to reach 72,000;
72,000 = 57e^0.88t
72,000/57 = e^0.88t
ln 126 = ln[e^0.88t]
4.8 = 0.88t
t = 4.8/0.88
t = 5.5 hours
Learn more about exponential growth;brainly.com/question/13674608
#SPJ1
4.6x^2+3.2-4x+2.7x^2-x=4.6x^2+3.2x+-4x+2.7x^2+-xCombine like terms:4.6x^2+3.2x+-4x+2.7x^2+-x=(4.6x^2+2.7x^2)+(3.2x+-4x+-x)=7.3x^2+-1.8xAnswer:7.3x^2-1.8x